2012
DOI: 10.1002/14651858.cd009468.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Male involvement for increasing the effectiveness of prevention of mother-to-child HIV transmission (PMTCT) programmes

Abstract: Male involvement for increasing the effectiveness of prevention of mother-to-child HIV transmission (PMTCT) programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 22 publications
2
35
1
Order By: Relevance
“…24 The high levels of male partner testing and couples testing achieved in this study are noteworthy since accessing male partners at clinics has proven challenging and provider-initiated strategies such as the provision of written invitations for partners or conducting home visits have either had limited success or are likely to require significant financial and human resources for implementation. 2527 These results suggest that provision of multiple self-tests to women attending antenatal and postpartum clinics should receive further consideration.…”
Section: Discussionmentioning
confidence: 98%
“…24 The high levels of male partner testing and couples testing achieved in this study are noteworthy since accessing male partners at clinics has proven challenging and provider-initiated strategies such as the provision of written invitations for partners or conducting home visits have either had limited success or are likely to require significant financial and human resources for implementation. 2527 These results suggest that provision of multiple self-tests to women attending antenatal and postpartum clinics should receive further consideration.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, evidence for the strategies’ effectiveness is sparse. A Cochrane systematic review (18) found only one study from Tanzania, an invitation card intervention, for inclusion in the review and concluded that further rigorous research is needed to inform evidence-based recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In communities where women are restricted from making independent HIV-related health decisions, the WHO, implementing partner organizations, and national health services have encouraged the inclusion of male partners in ANC services to increase uptake of PMTCT services, supplementing couples counseling whenever possible (6, 2428). Some, but not all, programs have resulted in improved PMTCT uptake (29, 30). Different models of male engagement have been implemented throughout sub-Saharan Africa (SSA) to increase partner accompaniment, including encouraging women to invite their own partners (4, 17), the use of clinic invitation letters (5, 31), and having community health educators/advocates visit couples’ homes to initiate testing recruitment and/or counseling (31, 32).…”
Section: Introductionmentioning
confidence: 99%
“…Different models of male engagement have been implemented throughout sub-Saharan Africa (SSA) to increase partner accompaniment, including encouraging women to invite their own partners (4, 17), the use of clinic invitation letters (5, 31), and having community health educators/advocates visit couples’ homes to initiate testing recruitment and/or counseling (31, 32). A systematic Cochrane review that reviewed a single eligible study from Tanzania cautioned that this strategy could lead to a paradoxical decreased uptake of ANC services, including HIV testing and PMTCT, if women feared participating in partners-based testing (30, 33). Engaging men may also lead to gender-based violence, if couples are serodiscordant (34, 35).…”
Section: Introductionmentioning
confidence: 99%